Implant success!!!.....simplified - Luthra Kaushal (Wolters Kluwer Medknow Publications, 2009)
The endeavor towards life-like restoration has helped nurture new vistas in the art and science of implant dentistry. The protocol of "restoration-driven implant placement" ensures that the implant is an apical extension of the ideal future restoration and not the opposite. Meticulous pre-implant evaluation of soft and hard tissues, diagnostic cast and use of aesthetic wax-up and radiographic template combined with surgical template can simplify the intricate roadmap for appropriate implant treatment. By applying the harmony of artistic skill, scientific knowledge and clinical expertise, we can simply master the outstanding implant success in requisites of aesthetics, phonetics and function.